Ultrasensitive label-free optical recording of bioelectric potentials using dioxythiophene-based electrochromic polymers - Yuecheng Zhou; Erica Liu; Anna M. Österholm; Austin L. Jones; Pengwei Sun; Yang Yang; Ching-Ting Tsai; Tomasz Zaluska; Wei Zhang; Holger Müller; John R. Reynolds; Bianxiao Cui (Nature Communications)
Abstract Dioxythiophene-based polymers are electrochromic, effectively converting electric potentials into optical signals through voltage-dependent changes in absorption. The electrochromic property of these π-conjugated polymers can be harnessed to transform miniscule bioelectric signals, such as neuronal action potentials, into optical readouts. To enhance sensitivity, we investigated the impact of backbone and side-chain chemistry of dioxythiophene-based polymers. Among them, P(OE3)-E, a copolymer of oligoether-functionalized 3,4-propylenedioxythiophene with unsubstituted 3,4-ethylenedioxythiophene, exhibits the highest electrochromic sensitivity for optical bioelectric potential detection. A crucial factor in optimizing detection sensitivity is aligning the electric potential that triggers the sharpest optical transition in electrochromic polymers with the redox potential of the biological environment. Using P(OE3)-E thin films, we reliably detected field potentials from isolated rat hearts, extracellular action potentials of stem cell-derived cardiomyocytes, and spontaneous action potentials of dissociated rat hippocampal neurons. Our results achieved a detection sensitivity of ~3.3 µV with sub-millisecond temporal resolution, matching that of traditional electrode-based recordings while eliminating the constraints of electrode patterning or placement. This work highlights the significant potential of π-conjugated polymers for advancing bioelectric detection technologies.